QRIS Dan Fenomena Cashless Society: Efisiensi Pembayaran Digital Terhadap Perspektif Gen Z - Luthfia Sabrina; Nurul Inayah; Muhammad Syahbudi (Politeknik Ganesha Medan, 2026)
This study aims to analyze the efficiency level of the QRIS (Quick Response Code Indonesian Standard) digital payment system from the perspective of Generation Z in Medan. The four main indicators measured were transaction speed, ease of use, transaction costs, and system convenience and reliability. This study used a descriptive quantitative approach with 100 active QRIS user respondents. The analysis results showed that QRIS had an overall efficiency level of 79.85%, categorized as